Public Relations Sebagai Pilar Reputasi dan Kepercayaan Publik - Siti Nurlaila; Eka Susilawati; Noerma Kurnia Fajarwati; April Laksana; Rizqi Fitrianti (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
.Public Relations (PR) plays a central role in shaping and maintaining the reputation and public trust of an organization. Through a conceptual approach and literature review, this article explores how PR functions as a strategic pillar in organizational communication. PR is not only responsible for delivering information but also for building mutual trust between organizations and the public through open, honest, and continuous communication. A strong reputation and high public trust are the result of consistent and responsive communication strategies. In the digital era, where misinformation and rapid information flow pose significant challenges, the role of PR becomes increasingly vital. The findings of this article suggest that strengthening the role of PR as a pillar of reputation and public trust should be a top priority in modern organizational communication strategies.